Innovative Ways of Improving Writing Skills (Journal of Pedagogical Inventions and Practices, 2023)
This article is about Writing. Writing is one way of providing variety in classroom procedures. It provides a learner with physical evidence of his achievements and he can measure his improvement. It helps to consolidate their grasp of vocabulary and structure, and complements the other language skills. Therefore, if a teacher is open to welcome new pedagogical innovations, he can provide goal-oriented introduction of innovative ideas into educational process. Lately, range of significant official acts was issued on accelerating and developing the foreign languages teaching; they define the state policy towards teaching foreign languages.